Positive and negative social reactions to salesperson deviance - Hochstein, Bryan W; Bonney, Leff; Clark, Melissa (Philadelphia: Taylor and Francis, 2015)
In this study, qualitative methods are used to gain a broader understanding of overall dimensions of salesperson deviant behaviors. Then reactions to the behaviors by others are explored, and contingent factors are identified that lead to either positive or negative social reactions and labels. This important aspect of salesperson deviance is explored to understand why some deviant behaviors are admired and others are shunned. Ultimately, this exploration of salesperson deviance contributes to the sales literature by developing a holistic model of salesperson deviance dimensions and the contingent factors that lead to positive and negative social reactions
Keywords: Salespeople -- Sales behaviour -- Personality psychology